Effects of rice hull addition on photodegradation and biodegradation of biopolymers in thermoplastified pectin (Research, Society and Development, 2023)
The high consumption of synthetic plastics has brought several harmful impacts; thus, the development of biodegradable packaging becomes important and necessary. The production of biopolymers using compounds such as pectin and silica has shown great potential for application. Rice husk, as a complementary source of silica, is being used as a mechanical reinforcement. This study aimed to prepare and characterize pectin films incorporated with rice husk and silica, in order to improve their properties with a focus on photo and biodegradation. And so, to evaluate the effects of adding these components on water vapor permeability (WVP), mechanical properties, thickness, color, photodegradation and biodegradation. The films were characterized and the results showed that the addition of rice husk and silica caused the biopolymers to have a perceptible color difference to the human eye (∆E between 1.5 and 5.0). The samples were yellowish and reddish and with intermediate luminosity. The incorporation of rice husk and silica caused an increase in thickness and WVP. It was observed that with this addition, the tensile strength and elongation at break decreased, and the modulus of elasticity increased. The results showed that the films showed a high rate of biodegradation and a low rate of photodegradation, that is, they are able to resist the action of light without altering their biodegradation. Thus, it was possible to observe that the films of pectin and rice husk or pectin and silica have the feasibility of application in several areas.